A Miniaturized Fractal Printed Circuit Board Antenna For Vo5g Applications - et. al., Vinoth M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A compact Fractal patch antenna is proposed for 5G applications operating in Sub-7 GHz band which covers IEEE P802.11 ay/D4.O standard applications and resonated exactly at 5.5 GHz with the wide band characteristic is achieved with the dimension of 13 x 19 x 1.6 mm3 and the dielectric material used in the proposed fractal antenna is FR4 with dielectric constant of 4.4. A defect is embedded in the ground plane and the antenna is stacked by the fractal technique. The experimentation of antenna have been carried out and results are in good agreement with the simulated results and the antenna real time efficiency rate is 61% and the structures are analyzed using HFSS v.20 which gives high accuracy in simulation.